INSTAGRAM DALAM PEMBENTUKAN IDENTITAS DIRI GENERASI Z - Damas Rambatian Rakanda; Christina Rochayanti; Kurnia Arofah (Jurnal Paradigma, 2020)
Instagram now become one of the popular social media among teenagers this time. Teenagers use Instagram as a means to show self existence and social life. at age teenagers Is age where teenagers search for self identity. So that is Instagram become one of the media of teenagers distributing their creativity. The purpose of this research is explain the establishment of the identity virtual teenagers users instagram in the Cawas village through social media Instagram. The theory used is the theory Identity Manuel Castell, theory New Media and contruction identity. This study using a method of descriptive qualitative. The result of this study discovered that in upload photos on instagram teenagers have the concept that they were going to spend. Environmental influences around become one of the factors that affects of teenagers in forming the selft identity. One of indicator that shows existence of informan by the number of Like and Followers. The informants most inspired by the influencer in terms of fashion and to process photos. Most of the feeds instagram informants contains the photos of himself. Existence it is important for teenagers, especially in social media instagram. Teenagers will look at its existence, along with its existence in social media Instagram.